ANTIBACTERIAL ASSAY OF KAYU CENDANA (SANTALUM ALBUM L.) EXTRACT - Partomuan Simanjuntak (Indonesian Journal of Pharmacy, 2003)
Identification of antibacterial compounds from cendana wood extract against Salmonella typhimurium, Escherichia coli, Kleibsiella sp. and Staphylococcus aureus had been conducted. The result showed that a and b-santalol was active against S. typhimurium and S. aureus where as epi-b-santalene is active against S. typhimurium.Key words : Santalum album; Santalaceae; Salmonella typhimurium; Escherichia coli; Klebsiella sp.; Staphylococcus aureus; a, b-santalol; epi-b-santalene